Seeking sunlight: rapid phototactic motility of filamentous mat-forming cyanobacteria optimize photosynthesis and enhance carbon burial in Lake Huron’s submerged sinkholes - Biddanda, Bopaiah A.; McMillan, Adam C.; Long, Stephen A.; Snider, Michael J.; Weinke, Anthony D. (Frontiers in Microbiology, 2015)
We studied the motility of filamentous mat-forming cyanobacteria consisting primarily of Oscillatoria-like cells growing under low-light, low-oxygen and high-sulfur conditions in Lake Huron’s submerged sinkholes using in situ observations, in vitro measurements and time-lapse microscopy. Gliding movement of the cyanobacterial trichomes (100-10,000 µm long filaments, composed of cells 10 µm wide and 3 µm tall) revealed individual as well as group-coordinated motility. When placed in a petri dish and dispersed in ground water from the sinkhole, filaments re-aggregated into defined colonies within minutes, then dispersed again. Speed of individual filaments increased with temperature from 50 µm minute-1 or 15 body lengths minute-1 at 10°C to 215 µm minute-1 or 70 body lengths minute-1 at 35°C – rates that are rapid relative to non-flagellated/ciliated microbes. Filaments exhibited precise and coordinated positive phototaxis towards pinpoints of light and congregated under the light of foil cutouts. Such light-responsive clusters showed an increase in photosynthetic yield – suggesting phototactic motility aids in light acquisition as well as photosynthesis. Once light source was removed, filaments slowly spread out evenly and re-aggregated, demonstrating coordinated movement through inter-filament communication regardless of light. Pebbles and pieces of broken shells placed upon intact mat were quickly covered by vertically motile filaments within hours and became fully buried in the anoxic sediments over 3-4 diurnal cycles – likely facilitating the preservation of falling debris. Coordinated horizontal and vertical filament motility optimize mat cohesion and dynamics, photosynthetic efficiency and sedimentary carbon burial in modern-day sinkhole habitats that resemble the shallow seas in Earth’s early history. Analogous cyanobacterial motility may have played a key role in the oxygenation of the planet by optimizing photosynthesis while favoring carbon burial.